Environmental Factors May Drive the Post-release Movements of Surrogate-Reared Sea Otters - Becker, Sarah L.; Nicholson, Teri E.; Mayer, Karl A.; Murray, Michael J.; Van Houtan, Kyle S. (Frontiers in Marine Science, 2020)
Southern sea otters (Enhydra lutris nereis) are currently >80% depleted with respect to both abundance and range occupancy baselines, challenging the long-term persistence of the species and the ecosystem benefits their populations might provide. From 2001-2018, the Monterey Bay Aquarium rescued stranded sea otter pups and reared them in captivity through a surrogacy program using non-releasable adult females. We gave 11,396 days of captive care to 56 otters, reintroduced them into the wild, and observed them over 894 total field days after release. This study describes the post-release movements of the 42 successfully released otters, quantifying their dispersal patterns and modeling environmental, demographic, and animal care influences through a machine learning framework. This random forest model specifically considers predictor variable correlation, accounts for individual and joint variable impacts, and evaluates robustness through sensitivity analyses. Heavy tailed dispersal models best explained the (n=641) daily movements of surrogate-reared otters, and the random forest outputs ranked population demography, population growth, and El Niño most significantly. Occasionally aided by recaptures, the scale of dispersals consistently declined after release, indicating successfully released otters stabilized their movements within three weeks in the wild. Our results show dispersal is an important metric for measuring the success of sea otter releases and suggest environmental factors (including climate) at release sites may determine the success of reintroduction programs.